Unveiling the menace: a thorough review of potential pandemic fungal disease - Mahdi Jafarlou (Frontiers in Fungal Biology, 2024)
Fungal diseases have emerged as a significant global health threat, with the potential to cause widespread outbreaks and significant morbidity and mortality. Anticipating future pandemic fungal diseases is essential for effective preparedness and response strategies. This comprehensive literature review aims to provide a comprehensive analysis of the existing research on this topic. Through an extensive examination of scholarly articles, this review identifies potential fungal pathogens that have the potential to become pandemics in the future. It explores the factors contributing to the emergence and spread of these fungal diseases, including climate change, globalization, and antimicrobial resistance. The review also discusses the challenges in diagnosing and treating these diseases, including limited access to diagnostic tools and antifungal therapies. Furthermore, it examines the strategies and interventions that can be employed to mitigate the impact of future pandemic fungal diseases, such as improved surveillance systems, public health education, and research advancements. The findings of this literature review contribute to our understanding of the potential risks posed by fungal diseases and provide valuable insights for public health professionals and policymakers in effectively preparing for and responding to future pandemic outbreaks. Overall, this review emphasizes the importance of proactive measures and collaborative efforts to anticipate and mitigate the impact of future pandemic fungal diseases.